Mitochondrial unfolded protein response gene CLPP changes mitochondrial dynamics and affects mitochondrial function - GuiJun Wu; Qing Xiong; XiaoJun Wei; Ye Wang; XueMei Hu; GuangZhen He; LinJie Liu; QianHui Lai; Zhe Dai; Dhakal Anushesh; Yancheng Xu (PeerJ, 2019)
Mitochondrial dynamics is associated with mitochondrial function, which is associated with diabetes. Although an important indicator of the mitochondrial unfolded protein response, to the best of our knowledge, CLPP and its effects on mitochondrial dynamics in islet cells have not been studied to date. We analyzed the effects of CLPP on mitochondrial dynamics and mitochondrial function in the mice islet β-cell line Min6 under high glucose and high fat conditions. Min6 cells were assigned to: Normal, HG, HG+NC, HG+siCLPP, HF, HF+NC and HF+ siCLPP groups. High glucose and high fat can promote the mRNA and protein expression of CLPP in mitochondria. The increase of mitochondrial fission, the decrese of mitochondrial fusion, and the damage of mintocondrial ultrastructure were significant in the siCLPP cell groups as compared to no-siCLPP treated groups. Meanwhile, mitochondrial functions of MIN6 cells treated with siCLPP were impaired, such as ATP decreased, ROS increased, mitochondrial membrane potential decreased. In addition, cell insulin secretion decreased and cell apoptosis rate increased in siCLPP groups. These results revealed that mitochondrial unfolded protein response geneCLPP alleviated high glucose and high fat-induced mitochondrial dynamics imbalance and mitochondrial dysfunction.